HOW PROFITABILITY, LIQUIDITY, AND INDEPENDENT BOARD OF COMMISSIONERS INFLUENCE MANUFACTURING FIRM VALUE? - Monica, Eva; Fauzi, Achmad; Zulaihati, Sri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to determine whether there is a partial or simultaneous influence of profitability, liquidity, and the independent board of commissioners on the company's value. The research method used in this study is a quantitative method, with secondary data sources consisting of financial reports, financial ratio reports, and corporate governance reports accessible through the website idx.co.id and the respective company websites for the research period from December 2020 to December 2022 using purposive sampling technique. The population used in this study consists of 48 companies over 3 periods with a total sample of 117. The data is processed using E-views 12 due to the use of panel data. The results of the study prove that profitability affects the company's value, liquidity does not affect the company's value, the independent board of commissioners affects the company's value, and profitability, liquidity, and the independent board of commissioners together affect the company's value.